Theoretical and practical meaning of ecological morphophysiological research og fish reproduction in the reservoir with ecology changed conditions - N. I. Rabazanov; M. M. Shihshabekov; D. M. Ramazanova; M. M. Nabiyev; B. I. Shihshabekova; D. R. Adueva (Юг России: экология, развитие, 2015)
Fish reproduction research showed that the change of existence conditions changes the character of sexual cell growth changes. Evident changes in the duration of protoplasmatic growth are observed as well as the asynchronism degree of sexual cells and their development rate during annual period.